Evaluation of prognostic factors in patients with osteosarcoma: the HUSM experience - Mohd Sofian, Azlan (2015)

(untitled)
Introduction: Osteosarcoma is a highly malignant primary bone tumour thus the evaluation of prognostic factors influencing the survival rates is extremely essential for defining the approach to the management of these patients. Despite the recent advancement in chemotherapy and improved prognosis, 30 - 40% of patients still succumb to the disease; therefore reliable prognostic factors would be essential to plan a more aggressive treatment in patients at a higher risk of failure of treatment. Among multiple variables evaluated in literatures, it is known that pulmonary metastases and chemo-necrosis are the best prognostic components on the survival. At present, there is no consensus on the prognostic significance of simple and cheap biochemical markers of pretreatment serum alkaline phosphate (ALP) and lactate dehydrogenase (LDH). This study analyzed the prognostic factors of particularly ALP and LDH and other general variable for prognosis and overall oncological outcome. Method: Clinical data of at least 5 years related to prognostic factors of 163 patients with osteosarcoma who were under follow-up under Hospital Universiti Sains Malaysia were retrospectively reviewed. This was a retrospective cohort study of all patients treated between January 2005 and December 2010. A total of 163 patients with the mean age of 18.9 years (range 6 – 59 years old) were evaluated. There were 109 males and 54 females. Majority of the patients were of Malay ethnic background (82.2%), compared to the Chinese (11.66%), followed by Indian ethnicity (4.29%). 55.2% of our patients presented with pulmonary metastases. In terms of type of surgery, 66.1% of our patients underwent limb salvage surgery and 33.9% underwent amputation. Results: The overall survival was 40.5%. The mean pre-treatment serum LDH level was 493.19 IU/L, and 52.8% of our patients had high values. The mean level of pre-treatment ALP was 273.93 IU/L, and 53% of our patients had high values. The 5-year overall survival rate of patients in the normal pre-treatment serum LDH group is 66.2%, whereas in the high pre-treatment serum LDH group is 17.4%. The 5-year overall survival rate of patients in the normal pre-treatment serum ALP group is 55.8 %, whereas in the high pre-treatment serum ALP group is 26.7%. In the multivariate statistical analysis, only the pre-treatment serum LDH and presence of metastasis maintained its prognostic significance as both the pre-treatment serum ALP and the type of surgery loses its independent predictive value. In regards to the other variables, 66.9% of our patients were male, with the overall survival of 39.4%. Our female patients had a similar overall survival of 42.6%. Pulmonary metastases presented in 90 patients (55.2%). The overall survival of these patients was 27.8% compared to 56.2% in those without metastatic disease. For patients who underwent limb-sparing surgery, their overall survival was 56.8%, whereas in the amputation group the overall survival was 17.6%. Conclusion: The overall survival of our osteosarcoma patients was influenced by the presence of pulmonary metastases and type of surgery. Pre-treatment serum LDH and ALP were of significant influence on the final survival. However age, gender, race, primary site of tumour, histological sub-type, were not of significant influence on the survival of our patients.